Far-Transfer Effects of Strategy-Based Working Memory Training - Chan, Sharon; Mueller, Ulrich; Masson, Michael E. J. (Frontiers in Psychology, 2019)
We assessed the transfer of working memory (WM) strategies that were trained in one context to a novel problem-solving task. Previous working-memory training studies have produced little evidence for transfer across task contexts. In the current study, 64 six- to nine-year-olds were randomly assigned to one of four training conditions: semantic and rehearsal training, semantic training only, rehearsal training only, and treated control group. All training groups performed significantly better on the transfer task than the control group, but training groups did not differ significantly from each other. Implications of the findings for cognitive interventions and future WM training studies are discussed.